Anatomy, histology and histochemistry of accessory sex glands in male Persian squirrel (Sciurus anomalus) - Akbari, Ghasem; Kianifard, Davoud (Italian Journal of Anatomy and Embryology, 2017)
Persian squirrel (Sciurus anomalus) is a species of squirrels in the Middle East. There is little information about the anatomy and histology of various organs of this species. Moreover, there are no practical data about the accessory male sex glands of this species of squirrel. In this study the anatomical, histological and histochemical properties of the male reproductive system accessory glands of Persian Squirrel was evaluated. Eight adult male squirrels were anesthetized and euthanized. The pelvic area was dissected and the male reproductive system was separated. The accessory sex glands were investigated for gross anatomical aspect. Samples were fixed in formaldehyde for histological and histochemical studies. The coagulating glands, prostate and bulbourethral glands were observed at gross anatomical level. A single heart-shape and compact prostate gland was situated on the dorsal side of pelvic urethra. Two small coagulating glands were observed on the cranio-dorsal side of prostate. Two large spiral shape bulbourethral glands were situated out of the pelvic cavity near the root of penis on both sides of anal area. Histologic studies revealed that all accessory sex glands were alveolar glands with cuboidal to columnar epithelium. The most positive reaction for PAS stain was observed in the trabeculae of glands. There was no positive reaction for lipids in glands stained with Oil red O and Sudan Black. Some anatomical differences were observed in the accessory sex glands of Persian Squirrel in comparison to other rodents, however the histology of glands was almost similar to other rodents.